Metabolic Syndrome and Cognitive Functions in Schizophrenia—Implementation of Dietary Intervention - Adamowicz, Katarzyna; Mazur, Aleksandra; Mak, Monika; Samochowiec, Jerzy; Kucharska-Mazur, Jolanta (Frontiers in Psychiatry, 2020)
Introduction: The co-existence of schizophrenia and metabolic syndrome is a widely described phenomenon that contributes to the worse functioning of patients in everyday life. A relatively new area of research is the relationship between metabolic syndrome (MS) and cognitive function in patients with schizophrenia. The aim of the study was to verify the relationship between the presence of metabolic syndrome and cognitive function of patients with schizophrenia and to assess the possibility of changing cognitive function by introducing appropriate dietary intervention. Materials and Methods: The study involved 87 individuals diagnosed with schizophrenia according to ICD-10 criteria, aged 19 to 67 years (M=41.67; SD=11.87). Patients were in the remission phase of schizophrenia, all using antipsychotics for pharmacological treatment. From a group of 60 patients with diagnosed metabolic syndrome (according to IDF criteria), 30 patients were randomly assigned to an experimental group with dietary intervention and control group without intervention, the remaining group was a comparison group. All groups were evaluated for cognitive function using Stroop Test, Trail Making Test (TMT), Verbal Fluency Test, Digit Span Backwards Test. In the experimental group a dietary intervention was applied, which was to provide the examined person with a 7-day dietary plan with reduced calorie content, in compliance with the Mediterranean diet. Results: After the dietary intervention there was a significant improvement in the number of errors made in the third Stroop Test (p<0.001), the time taken to complete the Point Linking Test was shortened (Test B; p=0,005), there was an improvement in Verbal Fluency Test in “animals” category (p=0,006) “sharp objects” category (p=0,009), the number of repeated digits has increased in Digit Span Test in “forward” category (p=0,001) and overall completion of the test (p=0,021). In the group of patients with MS without dietary intervention, the results of cognitive tests remained mostly unchanged. Conclusions: By changing the diet one can potentially influence cognitive performance in people with schizophrenia and metabolic syndrome.